Vietnam : Reading and Mathematics Assessment Study, Volume 3 - World Bank (Washington, DC, 2013)
This paper contains three volumes presenting the Vietnam Reading and Mathematics Assessment Study conducted in 2001. The first volume sets the study in its country context, describes its genesis, outlines the methodology, and summarizes the results. The main purpose is to show how the analysis of the study results points to specific policy interventions. The strong link between a teacher's subject knowledge, and the performance of her pupils argues for teacher upgrade programs, while the high variation of pupil performance between schools in the same province calls for local programs that improve school effectiveness. The first volume is followed by a second volume detailing the study results, and a third providing a full description of the study methodology.